Higher risk for incident heart failure and cardiovascular mortality among community‐dwelling octogenarians without pneumococcal vaccination. (21st September 2015) - Ahmed, Momanna B.; Patel, Kanan; Fonarow, Gregg C.; Morgan, Charity J.; Butler, Javed; Bittner, Vera; Kulczycki, Andrzej; Kheirbek, Raya E.; Aronow, Wilbert S.; Fletcher, Ross D.; Brown, Cynthia J.; Ahmed, Ali
Abstract: Aims: Octogenarians have the highest incidence of heart failure (HF) that is not fully explained by traditional risk factors. We explored whether lack of pneumococcal vaccination is associated with higher risk of incident HF among octogenarians. Methods and results: In the Cardiovascular Health Study (CHS), 5290 community‐dwelling adults, ≥65 years of age, were free of baseline HF and had data on pneumococcal vaccination. Of these, 851 were octogenarians, of whom, 593 did not receive pneumococcal vaccination. Multivariable‐adjusted hazard ratios (aHR) and 95% confidence intervals (CI) for associations of lack of pneumococcal vaccination with incident HF and other outcomes during 13 years of follow‐up were estimated using Cox regression models, adjusting for demographics and other HF risk factors including influenza vaccination. Octogenarians had a mean (±SD) age of 83 (±3) years; 52% were women and 17% African American. Overall, 258 participants developed HF and 662 died. Lack of pneumococcal vaccination was associated with higher relative risk of incident HF (aHR, 1.37; 95% CI, 1.01–1.85; P  = 0.044). There was also higher risk for all‐cause mortality (aHR, 1.23; 95% CI, 1.02–1.49; P  = 0.028), which was mostly driven by cardiovascular mortality (aHR, 1.45; 95% CI, 1.06–1.98; P  = 0.019). Octogenarians without pneumococcal vaccination had a trend toward higher risk of hospitalization due to pneumonia (aHR, 1.34; 95% CI, 0.99–1.81; P  = 0.059). These associations were not observed among those 65–79 years of age. Conclusions: Among community‐dwelling octogenarians, lack of pneumococcal vaccination was associated with a significantly higher independent risk of incident HF and mortality, and trend for higher pneumonia hospitalization.